Synthesis, Structural Characterization of 4’,4’’-Dibenzoylcurcumin and Assessment of its Complexation with Fe3+ and Cu2+ - Thuy, Pham Thu; Thang, Pham Chien; Ha, Nguyen Viet; Nguyet, Trieu Thi (VNU Journal of Science: Natural Sciences and Technology, 2019)
The curcumin derivative 4’,4’’-dibenzoylcurcumin (HL) was synthesized by the reaction between curcumin and benzoyl chloride in the presence of pyridine as a supporting base. The composition and structure of HL were characterized by spectroscopic methods such as IR, 1H and 13C NMR spectroscopy. Reactions of HL and transition metal ions, such as Fe3+ and Cu2+, in mixtures of CH3OH and CH2Cl2 gave rise to the corresponding complexes, compositions and structural features of which were studied by thermal analysis and IR spectroscopy. The results strongly suggested the obtained complexes with the compositions of [FeL3] and [CuL2]. In such compounds, metal ions coordinates with the deprotonated ligands L– through the donor sets (O,O) of the keto-enol moieties. Keywords: Curcumin, 4’,4’’-dibenzoylcurcumin, β-diketone, Fe(III) complexes, Cu(II) complexes. References [1] A. Goel, A.B. Kannumakkara, B.B. Aggarwal, Curcumin as “Curecumin”: From Kitchen to Clinic, Biochem. Pharmacol. 75 (2008) 787-809. https://doi.org/10.1016/j.bcp.2007.08.016. [2] T. Esatbeyoglu, P. Huebbe, I.M.A. Ernst, D. Chin, A.E. Wagner, G. Rimbach, Curcumin - From Molecule to Biological Function, Angew. Chem. Int. Ed. 51 (2012) 5308-5332. https://doi.org/ 10.1002/anie.201107724. [3] K. Priyadarsini, The Chemistry of Curcumin: From Extraction to Therapeutic Agent, Molecules 19 (2014) 20091-20112. https://doi.org/10.3390/ molecules191220091. [4] S. Wanninger, V. Lorenz, A. Subhan, F.T. Edelmann, Metal complexes of curcumin – synthetic strategies, structures and medicinal applications, Chem. Soc. Rev. 44 (2015) 4986-5002. https://doi.org/10.1039/C5CS00088B. [5] J. Wang, D. Wei, B. Jiang, T. Liu, J. Ni, S. Zhou, Two copper(II) complexes of curcumin derivatives: synthesis, crystal structure and in vitro antitumor activity, Transition Met. Chem. 39 (2014) 553-558. https://doi.org/10.1007/s11243-014-9831-z. [6] R. Pettinari, F. Marchetti, C. Pettinari, F. Condello, A. Petrini, R. Scopelliti, T. Riedel, P.J. Dyson, Organometallic rhodium(III) and iridium(III) cyclopentadienyl complexes with curcumin and bisdemethoxycurcumin co-ligands, Dalton Transactions 44 (2015) 20523-20531. https://doi.org/10.1039/C5DT03037D. [7] P.T. Thùy, P.C. Thắng, N.H. Huy, N.V. Hà, T.T. Nguyệt, Synthesis, structural characterization of 4,4’-diacetylcurcumin and its complexes with Fe(III), Co(II) (in Vietnamese), Vietnam Journal of Chemistry 55 (2017) 33-37. [8] P.C. Thắng, P.T. Thùy, T.T.K. Ngân, L.C. Định, Đ.T. Đạt, T.T. Nguyệt, Synthesis, structural characterization of 4’,4’’-dimethoxy-4-methylcurcumin and evaluation of its complexation with Co2+ and Cu2+ (in Vietnamese), Vietnam Journal of Chemistry 56 (2018) 113-117. [9] P.T. Thùy, P.C. Thắng, V.T.B. Ngoc, T.T. Nguyệt, Synthesis and structural characterization of a heteroleptic Pd(II) complex with 4,4’-diacetylcurcumin (in Vietnamese), Vietnam Journal of Chemistry 56 (2018) 119-123. [10] K. Singletary, C. MacDonald, M. Iovinelli, C. Fisher, M. Wallig, Effect of the beta-diketones diferuloylmethane (curcumin) and dibenzoylmethane on rat mammary DNA adducts and tumors induced by 7,12-dimethylbenz[a] anthracene, Carcinogenesis 19 (1998) 1039-1043. https://doi.org/10.1093/carcin/ 19.6.1039. [11] F. Payton, P. Sandusky, W.L. Alworth, NMR Study of the Solution Structure of Curcumin, J. Nat. Prod. 70 (2007) 143-146. https://doi.org/10. 1021/np060263s.